Cytogenetic and clinical features of down syndrome in malang, east java, indonesia - Ariani (Medical Faculty of Brawijaya University, Indonesia, 2022)
Introduction: Down syndrome (DS) is the most common chromosomal disorder. DS characterized by multiple congenital anomaly caused by trisomy 21This study was designed to evaluate the karyotype pattern, clinical features and risk factors of patients with Down syndrome. Method: Data were obtained from a retrospective analysis of a questionnaire from Down syndrome patients. Result: A total of 34 patients were studied, with 67,6% of males. Out of 34 patients, there were 25 children (73,5%) with no cytogenetic test, 4 children (11,7%) with lost cytogenetic test, 3 children (8,82%) with free trisomy (non-disjunction), 1 (2,9%) with translocation, and 1 (2,9%) with mosaics. Maternal age categories showed one mother less than 20 years, two mothers between 21-25 years, four mothers were between 25 and 30 years, 12 mothers were between 31 and 35 years, ten mothers were between 31 and 40 years, and five mothers were over 41 years of age. The most common clinical features in this study are Congenital Heart Disease (CHD), which was recognized in 9 (26,4%) patients with five patients had Atrial Septal Defect (ASD), two patients had ASD and Ventricular Septal Defect (VSD), two patients had Patent Ductus Arteriosus (PDA). All of them followed by dental problems in 8 (23,5%) patients, ophthalmology problems in 6 (17,6%) patients, digestive problems in 4 (11,7%) patients, seizure in 1 (2,9%) patient, hormonal problems in 1 (2,9%) patient, and hearing problem in 1 (2,9%) patient. There is no significant difference in CHD prevalence between each maternal age group (p = 0776, p>0.05). Conclusion: Down syndrome has a higher prevalence in males and is frequently seen among mothers between 31 -35 years of age, yet maternal age did not seem to influence CHD prevalence significantly. Early diagnosis and proper screening should be undertaken among these patients.